Pelatihan Desain Foto Produk UMKM Menggunakan Aplikasi Canva Pada PKK Papan Mas Bekasi - Sofica, Verra; Fauzi, Ahmad; Mukhayaroh, Anna; Fakhriza, Muhammad Hilman (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Community service activities at PKK RW 007 Tambun Selatan District aim to provide understanding and skills to PKK members regarding the use of the Canva application in designing photos of MSME products. The focus is on the PKK Board RW 007 Mas Tambun Selatan in Bekasi City. Activity participants are given practical training in using the Canva application, a user-friendly graphic design platform. In this training, PKK members teach how to create attractive product photo designs and support MSME promotions. Through the Canva application, they can easily edit images, add text, and create aesthetic designs without requiring in-depth graphic design skills. Using Canva aims to empower MSMEs in PKK RW 007 to increase the competitiveness of their products in the market. With an attractive design, it is hoped that MSME products can be more easily recognized and sought after by consumers. Apart from that, this training also provides an understanding of marketing strategies through social media and online platforms, so that MSME products can be reached by a wider market. The results of this activity are expected to have a positive impact, such as increasing sales and awareness among the public of PKK RW 007 MSME products Apart from that, this activity can also become social capital for PKK members to continue to develop skills in using technology to support the development of MSMEs in their environment.